Evaluation of paranasal sinus anatomic variations and mucosal changes with cone beam computed tomography - Tuğçe Temur Katibe; Evlice Burcu; Öztunç Haluk (Balkan Stomatological Society, 2022)
Background/Aim: Anatomical variations of paranasal sinuses are common and play an role in disrupting the drainage of the sinuses, which often causes chronic sinusitis. In this article, anatomical variations of the paranasal sinuses and its relationship with mucosal changes were evaluated retrospectively by cone beam computed tomography (CBCT) which is also known as dental volumetric tomography. Material and Methods: CBCT data of 500 patients who applied to Cukurova University Faculties of Dentistry for any reason were retrospectively evaluated by maxillofacial radiologist. Anatomical variants of paranasal sinuses were included in the study. Mucosal thickening greater than 2 mm in the maxillary sinus was considered pathological. Results: The most common anatomic variation in the study was the nasal septal deviation, found in 302 (60.4%) patients. The least common anatomic variation in the study was lower concha pneumatization found in 3 (0.6%) patients. Mucosal thickening of the maxillary sinus was observed in 271 (54.2%) cases in the right sinus and 260 (52%) cases in the left sinus (p>0.05). Conclusions: Nasal septum deviation was the most common variation in the study. According to the results of our study, concha bullosa, haller cell and the uncinate process had no definite effect on mucosal thickening in the maxillary sinus.